Green Navy sebagai Strategi Pertahanan Berkelanjutan : Tinjauan Literatur Teknologi Kapal Ramah Lingkungan - Tiwi Gustria Ningsih; Nurhazizah Yuslim (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Indonesia, as the world's largest archipelagic nation, holds a strategic position while simultaneously facing significant challenges in maintaining the sovereignty and security of its maritime territory. Increasingly complex maritime threats, such as illegal fishing, smuggling, and potential geopolitical conflicts, demand a transformation in maritime defense strategies to be more efficient and sustainable. In an era of increasing global awareness of the climate crisis, the maritime sector, including the defense sector, is being encouraged to decarbonize through the implementation of environmentally friendly ship technology. This research uses a literature review approach by examining various findings related to sustainable propulsion technology innovations relevant to the development of Indonesia's maritime defense fleet. The study results show that a hydrogen- and battery-based hybrid propulsion system can reduce carbon emissions by up to 73% and increase energy efficiency by 35%. In addition, wind-assisted propulsion sistem (WAPS) technology such as Flettner rotors and wing-sails contributes significantly to reducing fuel consumption by up to 30%, while extending ship cruising range without the need for intensive refueling. Meanwhile, the application of Computational Fluid Dynamics (CFD)-based propeller design optimization has been proven to reduce energy consumption by 13.2% and reduce noise levels by up to 15 dB, which greatly supports the needs of stealth operations in military missions. This study concludes that the implementation of environmentally friendly ship technology not only provides benefits in terms of energy efficiency and emission reduction, but also strengthens the operational resilience and strategic competitiveness of the Indonesian naval fleet amidst the dynamics of global maritime security. Thus, the Green Navy concept can be seen as a relevant and urgently needed sustainable defense strategy.